2020
DOI: 10.1177/0885066620903231
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Measurements and Their Association With Mortality in Pediatric Severe Sepsis in India: Evidence That 6-Hour Level Performs Best

Abstract: Purpose: To investigate association of static and dynamic lactate indices with early mortality (within 48 hours of admission), as well as need for vasopressors and mechanical ventilation in pediatric severe sepsis/shock. To explore optimal cutoffs of lactate indices. We hypothesized that dynamic indices are superior to static indices in predicting early mortality. Methods: This prospective cohort study involved children (aged <14 years) admitted in emergency department, tertiary care teaching hospital in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 35 publications
7
20
0
1
Order By: Relevance
“…We found that plasma lactate at 6 h > 2.5 mmol/L had a sensitivity 85% and a specificity 74% for mortality among septic children. Similar results have been reported in another study from India, 18 wherein the optimal cut-off of Lactate at 6 h for identifying early was 2.65 mmol/L mortality with 76% sensitivity and 85% specificity. Another significant observation was that plasma lactate at 6 h was better than lactate clearance for predicting in hospital mortality in septic children.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We found that plasma lactate at 6 h > 2.5 mmol/L had a sensitivity 85% and a specificity 74% for mortality among septic children. Similar results have been reported in another study from India, 18 wherein the optimal cut-off of Lactate at 6 h for identifying early was 2.65 mmol/L mortality with 76% sensitivity and 85% specificity. Another significant observation was that plasma lactate at 6 h was better than lactate clearance for predicting in hospital mortality in septic children.…”
Section: Discussionsupporting
confidence: 88%
“…A decreased plasma lactate clearance was shown to have a greater association with nonsurvival. Similar association between lactate and mortality is supported by findings yielded by other studies 10,13–18 . However, another study in children did not find lactate at admission to be significantly associated with hospital mortality in children with severe sepsis, although it was strongly correlated with PRISM III scores which have been established as valid predictor of mortality in children 19 …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The recent Sepsis-3 guidelines recommend that the persistence of a serum lactate levels >2 mmol/L, despite adequate fluid resuscitation, should be included as a new criterion in the clinical evaluation of septic shock.1 In this context, serum lactate is typically used to evaluate disease severity, treatment response, and prognosis. 26,27 In this study, plasma levels of glycocalyx components correlated significantly with lactate levels. These data suggest that the endothelial glycocalyx plays an important role in the pathophysiological progression of sepsis.…”
Section: Discussionsupporting
confidence: 49%